SnakeMap: four years of experience with a national small animal snake envenomation registry. Issue 9 (2nd August 2020) - Boller, M; Kelers, K; Stevenson, MA; Winkel, KD; Hardjo, S; Heller, J; Judge, PR; Ong, HM; Padula, AM; Reddrop, C; Santos, LCP; Sharp, CR; et al.
Abstract : SnakeMap is a national cloud‐based, veterinary snakebite registry. It was designed to prospectively collect data of the clinical circumstances and temporospatial information on cases of snake envenomation in dogs and cats. We herein introduce the project and summarise the data from the first 4 years of SnakeMap. The registry is a veterinary community‐based online database allowing case entry from veterinary hospitals across Australia. Registry data comprise hospital characteristics, patient characteristics, envenoming snake type, treatment and outcome variables, including time and geolocation of the snake bite. We present summative information on select key variables from the SnakeMap registry (1 July 2015 to 30 June 2019). Twenty‐eight hospitals from 6 states/territories entered 624 cases into the registry, including 419 dogs (67%) and 205 cats (33%). Bite time was available in 216 animals of which 90 (42%) were reported to be bitten in the 3 hours between 03:00 pm and 05:59 pm; median bite to presentation interval was 60 (interquartile range [IQR] 30, 211) minutes in dogs and 95 (IQR 41, 238) minutes in cats. Bites occurred in the owner's yard in 356 dogs (85%) and 53 cats (26%). A snake venom detection kit was used in 172 cases (28%) and antivenom was administered in 523 cases (85%). Most animals (n = 534, 88%) survived to discharge (median hospitalisation of 25 [IQR 16, 62] hours). SnakeMap effectively collects relevant clinical data from dogs and cats with presumed snake bite and provides locally specific information on the epidemiology of snake envenomation in small animals.